Experimental and numerical study of the compressive fatigue behavior of a Ti6Al4V mapped rhombioidal dodecahedral structure fabricated by electron beam melting - Yu, Boning; Li, Yuming; Abbès, Boussad; Li, Shujun; Yu, Baoyi (International Journal of Fatigue, 2023)
Triple-periodicarrayed porous structures are regarded as the most promising materials for the fabrication of medical bone implants. The fatigue properties of cellular structures are critical for their long-term use in dynamic biological skeletal environments. In this study, the rhomboidal dodecahedral cell structure of a Ti6Al4V alloy prepared by electron beam melting with different mapping ratios in one coordinate direction was homogenized. Based on this, the compressive fatigue behavior and fatigue failure mechanism under high cyclic loading were studied. To improve the fatigue performance and reduce the influence of residual stress, the microstructure was post-treated by cryogenization and characterized to analyze the evolution mechanism. The fatigue test results of the entire cell structure showed that failure was asynergy between fatigue damage and the ratchet effect. A change in the mapping ratio significantly affected the homogenization mechanical performance, which resulted in the fatigue properties. Based on the test results and numerical simulations, the cross-sectional elastic properties and local maximum stress of struts with different structural mapping ratios were expressed analytically. The fatigue life of the strut with the maximum local stress in the range of elastic deformation and that of the homogeneous block under the preset loading limit of the system were both modeled with appropriate material constants. The high-cycle fatigue life model was established to assist the fatigue behavior prediction of lattice structures.
Keywords: Analytical model; Electron beam melting; Fatigue behavior; Porous material; Titanium alloys